Past (pre)occupations, present (dis)locations : the nineteenth century restoried in texts from/about South Africa, Canada, Australia and Aotearoa New Zealand - Ellis, Jeanne (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.